Il fenomeno vita tra proprio e improprio, potenza e impotenza, singolare e comune - Prinzi, Salvatore (Fuori collana, 2022)
The dominant vision in our societies seems to conceive of life as a capital with which each individual would be endowed, as a collection of credits and skills that must be enhanced to produce performances characterized by ever greater speed, impact, and efficiency. Everything seems designed to increase a life of which we would be the masters, whose progress or regression can be evaluated according to quantitative criteria, in order to compare different lives and obtain the best possible selection. Thus, techniques are spreading everywhere that aim to enhance life, to make it more productive, while companies and institutions profit from every aspect of it. A frenzy that turns into its opposite, into a paradoxical sacrifice of life, into the loss of democratic control, of planning that looks to the future - as the pandemic and the war in Ukraine show us, revealing the limits of enhancement practices, the fragility of life, the inextricable connection between our lives, their belonging to a larger life of the species. If these events are the result of the ways in which life has been instituted, then, in these times when all of humanity is faced with health, war, and ecological challenges, the 'phenomenon life' should perhaps be rethought at its root, as an encounter rather than a competition, as recognition, as a communication.